PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS X TEKNIK MESIN SMK NEGERI 1 TANAH PUTIH KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Haryana, Gani; ', Jusmawati; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research problem was the low students learning achievement in social subject. This study was aim to improve learning outcomes IPS Mechanical Engineering students of class X SMK 1 Tanah Putih Tanah Putih Rokan Hilir with the implementation of cooperative learning model type STAD. This research is a classroom action research (PTK) is conducted in two cycles. Each cycle consists of two meetings and one-time delivery of content meeting the daily tests. Classroom action research in order to succeed, the researchers set the stage that action planning, action, observation and reflection. The instrument pengumupulan activity observation sheet data that teachers and students as well as achievement test. Based on the results, it was concluded that; 1) The application of the model type STAD cooperative learning can enhance the learning process. At the first meeting of the first cycle of teacher activity obtained percentage is 58.33% with enough categories, increased in the second meeting of the first cycle to 66.67% in both categories. At the first meeting of the second cycle increased to 87.50% with very good categories and increased in the second meeting of the second cycle with 95.83% peresentase very good category. While the activity of the first meeting I cycle students obtained percentage is 58.33% with enough categories, increased in the second meeting of the first cycle to 66.67% in both categories. At the first meeting of the second cycle increased again from previous meetings to 83.33% with very good categories and increased in the second meeting of the second cycle into 95.83% categorized very well and 2) Application of STAD type of cooperative learning model can improve student learning outcomes IPS X class 1 Mechanical Engineering SMK Tanah Putih Tanah Putih Rokan Hilir. Of the basic score to UH I with an average of 60.75 into 70.00 an increase of 15.22%; from basic score to UH II with an average of 60.75 into 82.50 is also an increase of 35.8 %.Key Words: Cooperative Learning Model Type STAD, Students Learning Achievement2